Persepsi Wisatawan Nusantara Terhadap Penyelenggaraan Pesta Kesenian Bali Sebagai Daya Tarik Wisata - I Wayan Rolly Yohan Kayansa; I Made Adikampana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
Chaiman of the PHRI (Indonesia Hotel and Restaurant Association)said that the Bali Arts festival is not a appropriate to serve as a tourist attraction. Based on this research aims to know the perception of tourist on the implementation of the Bali Arts Festival as a tourist attraction. The method in this study using a type of qualitative and quantitative data sources, the primary data, secondary data. The data collection is done by means of literature study, interviews, questionnaries, observations. Sampling technique in this study using a quota sampling, determine the sample using the formula Slovinwith the number of domestic tourists 50 people. Analysis of the data used is descriptive qualitative data analysis. The results showed that the Bali Arts Festival can be used as a tourist attraction, because the event can attract tourists to visit.Based on the questionnaire that has been distributed, the Bali Arts festival can be used as a tourist attraction for many tourists can find products by the people of Bali, both for the preservation of Balinese culture, and increase the economic income of local communities Keywords: Perception, Travelers Domestic, Bali Arts Festival, Tourist Attractions